Relationship between flowering, fruit setting and environmental factors on consecutive clusters in greenhouse tomato (Lycopersicon lycopersicum (L) Karsten) - Pék, Z.; Helyes, L. (International Journal of Horticultural Science, 2003)
The main season of greenhouse tomato begins late winter or early spring in the northern Temperate Zone. During this period decisive environmental factors affect flowering and fruit setting. In the present experiments, progress and dynamics of greenhouse tomato flowering and fruit set were examined in 1999 and 2001 spring. The beginning and the end of flowering and fruit set, the number of flowers and fruits set in each cluster were recorded. Flowering and fruit set characteristics were analysed with respect to the accumulated PAR and temperature were calculated for each cluster. One flower required 31.3 mol M-2 of accumulated PAR and 38 °C of sum temperature as an average for anthesis. One fruit required 27.9 mol m-2 of accumulated PAR and 33.3 °C of sum temperature as an average for fruit setting.